Pemindahan Ibu Kota Negara Maju dan Sejahtera - Muhammad Yahya (LP2M IAIN Palangka Raya, 2018)
The discourse to move the Indonesian capital city has repeatedly emerged. It occurs when critical events arise from social, political, environmental and disaster factors. The purpose of this study is to analyze how the discourse of Central Kalimantan as the Indonesian capital city. The method of this research uses qualitative approach with library research analysis. It uses primary books on public feasibility of an area becoming capital city of Indonesia. The results of this study with spatial, ecological and territorial approach, where Jakarta as a consideration for discussion. So in the temporary hypothesis, Jakarta is less feasible as the capital city of the country. Meanwhile, Central Kalimantan becomes alternative city to be the capital city. It is representative of its vast territory, not vulnerable to natural disasters, added a small population of its citizen.